Breaking the dormancy of grapevine (Vitis vinifera L.) budswith the application of garlic extract (AlliumsativumL.) under tropical high-altitude conditions - Almanza M., Pedro José; Serrano C., Pablo Antonio; Fischer, Gerhard; Balaguera-López, Helber Enrique (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2010)
Grapes for winemaking have been growing over the past 25 years in 18 municipalities of Boyacá (Colombia). The climatic conditions of high elevations in tropical zones do not provide cold enough conditions, resulting in low and irregular bud breaking, and generating low and uneven yields. Garlic has been recognized as an inducer of bud breaking, but it has not been evaluated under tropical conditions. Therefore, this study evaluated the effect of garlic extract on the induction of breaking bud dormancy in the clonal grape variety Riesling x Silvaner in the municipality of Corrales (Boyacá). A completely randomized design was used with four treatments (garlic extract 100%, garlic extract 50%, hydrogen cyanamide and control) with five repetitions. Treatments were applied directly on the buds immediately after pruning, using a brush. The percentage of bud breaking (PBB), average time of bud breaking (ATB), average speed of bud breaking (ASB), leaf area, and number of leaves, shoots and panicles were determined.With statistical differences, the application of garlic 50%had significantly the highest PBB, the lowest ATB and the higher ASB, and, without statistical differences, favorable responses were found in leaf area, number of leaves, shoots and trusses of grape plants. It can be concluded that the application of garlic is an important alternative in the induction of bud breaking in the Riesling x Silvaner variety.